Evaluasi Kepatuhan Syariah pada Akad Musyarakah dalam Pembiayaan Usaha Mikro - Halimah Halimah; Defina Alfiyanti; Serly Amelika Putri; Muhamad faozi alrizki; Falah Alkautsar; Dian Agustin; Viandilan Viandilan; Feby Aristrianti; Afif al khaedar; Mohammad Ridwan; Abu Lubaba (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to evaluate the level of sharia compliance in musyarakah contracts within micro-enterprise financing. Musyarakah is a partnership-based financing contract that emphasizes cooperation, profit-sharing based on an agreed ratio (nisbah), and proportional risk sharing in accordance with each party’s capital contribution. In practice, the implementation of musyarakah contracts in micro-enterprise financing must be assessed against the Fatwa of the National Sharia Council–Indonesian Ulema Council (DSN-MUI), principles of fiqh muamalah, and Islamic banking regulatory frameworks in Indonesia. The findings show that the implementation of musyarakah working capital financing in Islamic banking is generally in the good category. However, two non-compliance issues with sharia principles were identified. First, there is an imbalance in work participation, where the business is fully managed by the customer while the bank only provides supervision and guidance without active involvement, whereas active participation of partners is a fundamental principle of musyarakah. Second, there is an element of riba due to the use of a fixed profit-sharing scheme, even though profits in musyarakah should be uncertain and based on actual business performance. The study implies that Islamic banks need to improve musyarakah implementation to ensure full compliance with DSN-MUI fatwas, particularly in terms of active bank participation and non-fixed profit-sharing arrangements. Properly implemented, musyarakah financing can strengthen micro and small enterprises by promoting justice-based and risk-sharing economic cooperation.